Financial Statement Quality in the Hospitality Industry - Rosmiati Pakata (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to prove the influence of the quality of human resources, control systems internal, utilization technology And commitment organization to quality report finance. Study it uses primary data. The population in this study were finance employees at 69 hotels in Garut Regency. The number of samples uses the Slovin formula, so the number of samples based on calculation is 32 employee. Method analysis Which used in study This is multiple regression analysis with a significance level of 4%. The results of this study indicate that quality human resources and the use of technology have a positive effect while the control system internal And commitment organization No influential to quality report finance. Need done study with respondent Which more wide so that results can generalized on industry hospitality.